A Comparative Analysis of Mediation: Examination and critique of the Theory and Practice in Germany, Switzerland and Scotland - Carle, Dominik Helmut (Tectum Verlag, 2017)
To harmonize the rules on mediation within the European Union, Directive 2008/52/EC was created imposing mandatory standards on certain aspects of mediation. The Directive is binding only in respect of cross-border dispute mediations, but its provisions may also be applied to internal dispute mediation processes. This led to the monistic approach, where a legislation system simultaneously seeks to regulate both internal dispute and cross-border dispute mediations and thus treats them equally, and the dualistic approach, where cross-border dispute mediations are regulated separately, and thus internal dispute and cross-border dispute mediations may be treated differently. The implementation of Directive 2008/52/EC by the monistic approach in Germany, and by the dualistic approach in Scotland, and the autonomous handling of mediation legislation in Switzerland (which is not bound by Directive 2008/52/EC) show different patterns of development with regard to mediation in Europe. The comparison between those developments finally answers the question whether Directive 2008/52/EC in its current form was appropriate. The present monograph, which was honoured with a distinction by the University of Glasgow, stems from a research project on mediation in collaboration with Professor Janeen Carruthers.